Retrieval of separated instrument from the root canal using ultrasonics: Report of three cases - Ashtha Arya; Anshul Arora; Gourav Thapak (Wolters Kluwer Medknow Publications, 2019)
One of the most frequent mishaps during root canal procedure is the separation of an endodontic instrument during biomechanical preparation. It prevents proper debridement of the canal apical to the fragment and compromises the success of the treatment. Development in techniques and armamentarium has led to successful retrieval of separated instrument from the root canal. Adequate knowledge, good clinical skill, and experience enable good management of instrument fractured in the root canal. In this report, we present three cases with separated instruments in the root canal which were successfully retrieved with the use of ultrasonics under magnification.